Catalysis and catalytic processes - Ranade, V. V.; Joshi, S. S. (Industrial catalytic processes for fine and specialty chemicals, 2016)
Catalytic reactions are ubiquitous in chemical and allied industries. A homogeneous or heterogeneous catalyst that provides an alternative route of reaction with lower activation energy and better control of selectivity can make a substantial impact on process viability and economics. In this chapter, the basics of catalysis and catalytic processes are introduced. Some aspects of reaction and reactor engineering required to realize catalytic processes in practice are also discussed. In addition, the organization of the book is outlined.